Guillain-Barre syndrome following COVID-19 vaccines: A review of literature - Yu, Miao; Nie, Shuang; Qiao, Yue; Ma, Ying (Frontiers in Immunology, 2023)
Objective: This study aimed to retrospectively analyze reported Guillain–Barré syndrome (GBS) cases that occurred after COVID-19 vaccination. Methods: Case reports of GBS following COVID-19 vaccination that were published before May 14, 2022, were retrieved from PubMed. The cases were retrospectively analyzed for their basic characteristics, vaccine types, the number of vaccination doses before onset, clinical manifestations, laboratory test results, neurophysiological examination results, treatment, and prognosis. Results: Retrospective analysis of 60 case reports revealed that post-COVID-19 vaccination GBS occurred mostly after the first dose of the vaccination (54 cases, 90%) and was common for DNA vaccination (38 cases, 63%), common in middle-aged and elderly people (mean age: 54.5 years), and also common in men (36 cases, 60%). The mean time from vaccination to onset was 12.3 days. The classical GBS (31 cases, 52%) was the major clinical classification and the AIDP subtype (37 cases, 71%) was the major neurophysiological subtype, but the positive rate of anti-ganglioside antibodies was low (7 cases, 20%). Bilateral facial nerve palsy (76% vs 18%) and facial palsy with distal paresthesia (38% vs 5%) were more common for DNA vaccination than for RNA vaccination. Conclusion: After reviewing the literature, we proposed a possible association between the risk of GBS and the first dose of the COVID-19 vaccines, especially DNA vaccines. The higher rate of facial involvement and a lower positive rate of anti-ganglioside antibodies may be a characteristic feature of GBS following COVID-19 vaccination. The causal relationship between GBS and COVID-19 vaccination remains speculative, more research is needed to establish an association between GBS and COVID-19 vaccination. We recommend surveillance for GBS following vaccination, because it is important in determining the true incidence of GBS following COVID-19 vaccination, as well as in the development of a more safer vaccine.